2008
DOI: 10.1136/aim.26.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Is it All about Sex? Acupuncture for the Treatment of Pain from a Biological and Gender Perspective

Abstract: Pain is a unique personal experience showing variability where gender and sex related effects might contribute. The mechanisms underlying the differences between women and men are currently unknown but are likely to be complex and involving interactions between biological, sociocultural and psychological aspects. In women, painful experimental stimuli are generally reported to produce a greater intensity of pain than in men. Clinical pain is often reported with higher severity and frequency, longer duration, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 137 publications
1
24
3
Order By: Relevance
“…Since both disorders are female predominant, it is observed that menstrual cycle does enhance their pain severity 22,65. Consequently, sex steroids likely play a role to modulate the nociception leading to an enhanced symptoms among the females particularly occurring in their cycles, while their psychosocial factors may additionally modify the finally perceived pain sensation 22,66…”
Section: Symptoms and Diagnosesmentioning
confidence: 99%
See 1 more Smart Citation
“…Since both disorders are female predominant, it is observed that menstrual cycle does enhance their pain severity 22,65. Consequently, sex steroids likely play a role to modulate the nociception leading to an enhanced symptoms among the females particularly occurring in their cycles, while their psychosocial factors may additionally modify the finally perceived pain sensation 22,66…”
Section: Symptoms and Diagnosesmentioning
confidence: 99%
“…Besides, the visceral sensitivity is usually gender determined since sexual steroids may enhance its perception among the female IBS subjects 65,66,81. On the other hand, migraine, a primary brain dysfunction, is an interictal hypersensitivity to some sensory stimuli leading to the episodic activation and sensitization of trigemino-vascular pain pathway and the following headache consequences 61,62.…”
Section: Pathogenesesmentioning
confidence: 99%
“…It has been suggested that gender differences in coping styles and resources may explain the higher occurrence of IBS symptoms and prevalence of this syndrome in women as compared to men (Adeyemo, Spiegel, & Chang, 2010; Lund & Lundeberg, 2008; Rao, 2009). How sex (e.g., ovarian hormones) and/or gender (e.g., social role) contribute to the female predominance in IBS remains to be determined.…”
Section: Gender Differences In Ibsmentioning
confidence: 99%
“…Women typically have a lower pain threshold (that is, a greater sensitivity to experimentally induced pain) than men [14]. This may be mediated by sociocultural factors (including age, family history, and gender roles), psychological factors (such as anxiety, depression, cognition, behavior), or biological factors (like genetics, sex hormones, endogenous pain inhibition), all of which can also interact with each another in complex ways [27].…”
Section: Introductionmentioning
confidence: 99%